miR-17-92 cluster in osteoarthritis: Regulatory roles and clinical utility - Pan, Xuefeng; Cen, Xiao; Xiong, Xiner; Zhao, Zhihe; Huang, Xinqi (Frontiers in Genetics, 2022)
Osteoarthritis (OA) is the most prevalent articular disease especially in aged population. Caused by multi-factors (e.g., trauma, inflammation, overloading), OA leads to pain and disability in affected joints, which brings about decreased patients’ quality of life and increased social burden. In pathophysiology, OA is mainly characterized by cartilage hypertrophy or defect, subchondral bone sclerosis and synovitis. The homeostasis of cell-cell communication is disturbed as well in such pro-inflammatory microenvironment, which provides clues for the diagnosis and treatment of OA. MicoRNAs (miRNAs) are endogenous non-coding RNAs that regulate various processes via post-transcriptional mechanisms. miR-17-92 cluster is a miRNA polycistron encoded by host gene called MIR17HG. Mature miRNAs generated from MIR17HG participate in biological activities such as oncogenesis, neurogenesis and modulation of immune system. Accumulating evidence also indicates that the expression level of miRNAs in miR-17-92 cluster is tightly related to the pathological processes of OA, such as chondrocyte apoptosis, extracellular matrix degradation, bone remodeling, synovitis, et al. In this review, we aim to summarize the roles of miR-17-92 cluster in the underlying molecular mechanism during the development and progression of OA and shed light on the new avenue of the diagnosis and treatment of OA.